Phenomena identification and categorization by the required level of multiphysics coupling in FHR modeling and simulation. (November 2018) - Rahnema, Farzad; Sun, Xiaodong; Petrovic, Bojan; Diamond, David; Bajorek, Stephen; Guo, Yujun; Yoder, Graydon; Zhang, Dingkang; Burke, Paul
Abstract: This study identifies the phenomena that impact the accuracy of the multiphysics analysis of fluoride salt-cooled high temperature reactors (FHR) and categorizes the level of coupling needed to model these phenomena with sufficient accuracy in the context of three scenarios, namely, normal operation, station blackout, and simultaneous withdrawal of all control rods. Such a study is a necessary step prior to developing or extending existing multiphysics modeling and simulation tools. The identified multiphysics phenomena are categorized into the groups requiring "tight" and "loose" coupling. "Tight" coupling refers to phenomena that require iterative feedback between multiple physics modules/methods whereas "loose" coupling refers to phenomena that require only data from other physics that can be pre-calculated and shared in tabular or functional form. For the station blackout scenario, it was determined that no identified phenomena required tight coupling. For the rod withdrawal and normal operation scenarios, it is found that there is a large number of phenomena that require tight coupling between neutronics and thermal hydraulics.